The Role Of Non Judge Mediators Providing Guarantee Of Women's Rights Protection In Divorce Cases - Joko Sulistiono; Akhmad Haries; Maisyarah Rahmi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2022)
The mediation process encountered obstacles. The role of non-judge mediators to protect women's rights in divorce cases was needed in the mediation process. This study aims to determine the role of non-judge mediators in providing guarantees for the protection of women's rights in divorce cases at the Samarinda Religious Court and to find out the obstacles to guaranteeing the protection of women's rights that occur in the mediation process in divorce cases at the Religious Courts. This type of research is normative empirical using descriptive qualitative research methods with data collection techniques in the form of observation, interviews, documentation, supported by legislation and legal norms in society. Research Qualitative data analysis techniques, in the process of analysis with data reduction (selection process). The results obtained from this study are that the role of non-judge mediators at the Samarinda Religious Court has provided protection for post-divorce women's rights in cases of talak and divorced divorces with the same rights. Obstacles in the mediation process to protect women's rights after divorce, namely the purpose of the Religious Courts is only to formalize Divorce in state law, the absence of good faith from one party can be caused by not wanting to divorce or not wanting to meet again with other parties, the inability of the parties economically to fulfill women's rights after divorce.